Behavioral and Pharmacokinetic Profile of Indole-Derived Synthetic Cannabinoids JWH-073 and JWH-210 as Compared to the Phytocannabinoid Δ9-THC in Rats - Uttl, Libor; Szczurowska, Ewa; Hájková, Kateřina; Horsley, Rachel R.; Štefková, Kristýna; Hložek, Tomáš; Šíchová, Klára; Balíková, Marie; Kuchař, Martin; Micale, Vincenzo; Páleníček, Tomáš (Frontiers in Neuroscience, 2018)
Synthetic cannabinoid compounds are marketed as “legal” marijuana substitutes, even though little is known about their behavioral effects in relation to their pharmacokinetic profiles. Therefore, in the present study we assessed the behavioral effects of systemic treatment with the two synthetic cannabinoids JWH-073 and JWH-210 and the phytocannabinoid Δ9-THC on locomotor activity, anxiety-like phenotype (in the open field) and sensorimotor gating (measured as prepulse inhibition of the acoustic startle response, PPI), in relation to cannabinoid serum levels. Wistar rats were injected subcutaneously (sc.) with JWH-073 (0.1, 0.5, or 5 mg/kg), JWH-210 (0.1, 0.5, or 5 mg/kg), Δ9-THC (1 or 3 mg/kg) or vehicle (oleum helanti) in a volume of 0.5 ml/kg and tested in the open field and PPI. Although JWH-073, JWH-210, Δ9-THC (and its metabolites) were confirmed in serum, effects on sensorimotor gating were absent, and locomotor activity was only partially affected. Δ9-THC (3 mg/kg) elicited an anxiolytic-like effect as suggested by the increased time spent in the center of the open field (p < 0.05). Our results further support the potential anxiolytic-like effect of pharmacological modulation of the endocannabinoid system.